2019
DOI: 10.1002/we.2336
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of log‐of‐power extremum seeking control for wind turbines using large eddy simulations

Abstract: The extremum seeking control (ESC) algorithm has been proposed to determine operating parameters that maximize power production below rated wind speeds (region II). This is usually done by measuring the turbine's power signal to determine optimal values for parameters of the control law or actuator settings. This paper shows that the standard ESC with power feedback is quite sensitive to variations in mean wind speed, with long convergence time at low wind speeds and aggressive transient response, possibly uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Yang et al (2015) demonstrated the benefits of the NLESC wind farm control strategy via SimWindFarm simulation. Later studies with LES simulations further validated the effectiveness (Ciri et al, 2016, 2017, 2019).…”
Section: Introductionmentioning
confidence: 84%
“…Yang et al (2015) demonstrated the benefits of the NLESC wind farm control strategy via SimWindFarm simulation. Later studies with LES simulations further validated the effectiveness (Ciri et al, 2016, 2017, 2019).…”
Section: Introductionmentioning
confidence: 84%
“…The ESC algorithm is based on maximization of a performance index of linear or nonlinear dynamic systems through the search for optimal control inputs 53 . For the system under investigation, the performance index to be maximized is designed as a concave function of the turbine rotor power 47,52 as follows: J=σPrat2σPratPnormalr2, where P rat is the rated turbine power and σ is a constant slightly greater than unity. The maximum magnitude of this performance index occurs at P r equals σP rat , thus the controller allows the turbine to harvest slightly more power than P rat to compensate for drivetrain losses.…”
Section: Control System Designmentioning
confidence: 99%
“…To achieve this objective, the control strategy should be able to confront the nonlinear dynamics of the wind turbine and the nonminimum phase behavior of the drivetrain's hydrostatic CVT unit 46 . Compared with many control strategies, extremum‐seeking control (ESC) represents a promising control strategy for wind energy systems, 47–52 which operates independent of wind speed measurement and has been validated experimentally. The ESC strategy is a model‐free real‐time optimal control strategy 53 based on a gradient search approach.…”
Section: Introductionmentioning
confidence: 99%
“…However, the plant or the device could be operating under wide variability of conditions (such as changing wave heights or periods), and the resulting power can vary in different orders of magnitude. As suggested by Ciri et al [40], the purpose of the logarithmic function is to limit the variation of the performance metric drastically, which avoids re-tuning ES hyper-parameters for changing operating conditions of the plant.…”
Section: Extremum-seeking Control Algorithmsmentioning
confidence: 99%